Identification of cytochrome CYP2E1 as critical mediator of synergistic effects of alcohol and cellular lipid accumulation in hepatocytes in vitro - Mahli, Abdo; Thasler, Wolfgang E.; Patsenker, Eleonora; Mueller, Sebastian; Stickel, Felix; Müller, Martina; Seitz, Helmut K.; Cederbaum, Arthur I.; Hellerbrand, Claus (OncoTarget, 2015)
Clinical studies propose a causative link between the consumption of alcohol and the development and progression of liver disease in obese individuals. However, it is incompletely understood how alcohol and obesity interact and whether the combined effects are additive or synergistic. In this study, we developed an in vitro model to address this question. Lipid accumulation in primary human hepatocytes was induced by incubation with oleic acid. Subsequently, steatotic and control hepatocytes were incubated with up to 50 mM alcohol. This alcohol concentration on its own revealed only minimal effects but significantly enhanced oleate-induced lipogenesis and cellular triglyceride content compared to control cells. Similarly, lipid peroxidation, oxidative stress and pro-inflammatory gene expression as well as CYP2E1 levels and activity were synergistically induced by alcohol and steatosis. CYP2E1 inhibition blunted these synergistic pathological effects. Notably, alcohol and cellular steatosis also induced autophagy in a synergistic manner, and also this was mediated via CYP2E1. Further induction of autophagy ameliorated the joint effects of alcohol and oleic acid on hepatocellular lipid accumulation and inflammatory gene expression while inhibition of autophagy further enhanced the dual pathological effects. Further analyses revealed that the joint synergistic effect of alcohol and steatosis on autophagy was mediated via activation of the JNK-pathway. In summary, our data indicate that alcohol induces not only pathological but also protective mechanisms in steatotic hepatocytes via CYP2E1. These findings may have important implications on the prognosis and treatment of alcoholic liver disease particularly in obese individuals.
Gesehen am 04.06.2020